Pengaruh Variasi Produk, Kualitas Pelayanan dan Kualitas Produk terhadap Keputusan Pembelian pada PT. Lautan Biru Raya - Jaka Permana; Steven Jourdan; Ivana Theja (IPM2KPE, 2024)
The purpose of this research is to determine the influence of product variations, service quality and product quality on purchasing decisions at PT Lautan Biru Raya. Product variety is a key element in the pharmaceutical distribution industry. The research method uses quantitative methods with a sample size of 105 customers. Data testing was carried out by carrying out classic assumption tests, regression tests and hypothesis testing using SPSS. The results of the research partially show that product variety, service quality and product quality have a significant influence on purchasing decisions. Conclusion, that product variety, service quality and product quality have a significant influence on purchasing decisions. Keywords: Service Quality, Product Quality, Purchasing Decisions, Product Variations